Implementasi Pendekatan Partisipatif Teknik True False Sebagai Upaya Meningkatkan Hasil Belajar Keterampilan Komputer dan Pengelolaan Informasi (KKPI) Siswa Kelas XIMM4 SMK Negeri 1 Sawan Tahun Ajaran 2012/2013 - Putu Soni Ermawati; Luh Putu Eka Damayanthi; Made Windu Antara Kesiman; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This Classroom Action Research aims to: 1) improve student learning outcomes through True False techniques partisiatif approach, 2) determine students' response to the approach of Participatory Techniques True False. This study was conducted to further increase student participation in the learning KKPI through card statement containing the statement is true or false.  This study was classroom action research, which took place in the SMK N 1 Sawan and was taken in 2nd semester in the academic year 2012/2013. The subject of this research was the XIMM4th grade students of SMK N 1 Sawan in the academic year 2012/2013 with the object were result study research and the students’ response. The data of the students’ result study was collected by the test in every end of the cycle and the students’ response was collected by closed questionnaire.   The results showed that: (1) student learning outcomes has increased from cycle I to cycle II (2) The response of students to the True False Techniques Participatory approaches in KKPI subjects are in positive qualification.